Eco-friendly Management of Banana Anthracnose (Colletotrichum musae) Using Bio-Rationals - Karthika, T.; Thiruchchelvan, N.; Mikunthan, G. (University of Jaffna, 2020)
Banana anthracnose caused by Colletotrichum musae (Berk. & M.A.Curtis) Arx is the most serious postharvest disease of immature and mature banana fruits, causing a loss of 30-40% of marketable fruits in Asia. The aim of this study was to determine in-vitro antifungal activity of aqueous leaf extracts of selected plant species and to test the antagonistic potential of Trichoderma viride against C. musae. Aqueous leaf extracts were obtained from Lantana camera, Piper betle, Azadiracta indica and Cinnamomum zeylanicum and antifungal activity was determined using poison food technique at 5%, 10%, 15% and 20% concentration in potato dextrose agar under in-vitro conditions with three replicates. The results revealed that five days of post-inoculation, all four plant species showed stronger antifungal activity against C. musae as opposed to the control. Within the selected concentration, 20% aqueous leaf extracts of L. camera, P. betle, A. indica, C. zeylanicum showed excellent inhibitory activity against C. musae. Complete mycelial growth inhibition of C. musae was observed in leaf extracts of C. zeylanicum (100%), P. betle (100%) followed by L. camera (60%). In addition, T. viride gave promising results in controlling the growth of C. musae in dual culture under in-vitro condition (91%). Based on the results, the selected plant aqueous leaf extracts at 20% concentration could be developed and used as an effective bio-rational to manage the post-harvest anthracnose disease in banana. In future in-vivo studies are needed to test the efficacy of these bio-rationals under the field conditions.
Keywords: Anthracnose; Bio-agents; Botanicals; Colletotrichum musae; Trichoderma viride